Cytopathogenicity of classical swine fever virus caused by defective interfering particles. - Meyers, G (1995)
For three independent cytopathogenic isolates of classical swine fever virus, defective RNAs were found in infected cells in addition to full-length viral genomes. These RNAs represent the genomes of typical defective interfering (DI) particles because of strict dependence on a complementing helper virus and interference with the replication of the helper virus. Analysis of the DI genomes revealed internal deletions of 4,764 nucleotides encompassing the complete structural protein-coding region of the virus and two flanking nonstructural genes. Plaque isolation and RNA transfection experiments showed that the DI particles are responsible for the cytopathic effect caused by these classical swine fever virus isolates.